A phase 2 study of epothilone B analog BMS‐247550 (NSC 710428) in patients with relapsed aggressive non‐Hodgkin lymphomas. Issue 9 (10th January 2013) - Churpek, Jane E.; Pro, Barbara; van Besien, Koen; Kline, Justin; Conner, Kathy; Wade, James L.; Hagemeister, Fredrick; Karrison, Theodore; Smith, Sonali M.
Abstract BACKGROUND: The management of relapsed aggressive lymphomas remains problematic. Ixabepilone (BMS‐247550, epothilone B analog), a potent inhibitor of tubulin disassembly, has promising preclinical and early‐phase clinical activity in drug‐resistant malignancies. METHODS: This multicenter phase 2 clinical trial tested the activity and safety of ixabepilone in relapsed/refractory aggressive lymphoma patients with either chemosensitive (at least a partial response [PR] to most recent chemotherapy) or chemoresistant (less than PR to most recent chemotherapy) disease at 20 mg/m2 given intravenously weekly on days 1, 8, and 15 of a 28‐day cycle. RESULTS: Fifty‐one enrolled patients with a median age of 66 years received at least 1 dose of ixabepilone. Diffuse large B‐cell lymphoma (n = 25; 49%), mantle cell lymphoma (n = 16; 31%), and transformed follicular lymphoma (n = 5; 10%) were the most frequent histologies. Patients were heavily pretreated, with more than one‐quarter having received 4 or more prior therapies. The overall response rate was 27% (14 of 51 patients) with 12% (6 patients) experiencing complete responses and 16% (8 patients) with PRs. All responses were in patients with chemosensitive disease. The median time to response was 2 cycles with a median duration of response of 9.7 months. CONCLUSIONS: Ixabepilone was well‐tolerated, with neutropenia, peripheral sensory neuropathy, fatigue, and nausea as the major toxicities. Ixabepilone has modest single‐agent activity in patients with recurrent chemosensitive aggressive lymphomas. Cancer 2013. © 2013 American Cancer Society.